Pengaruh Kinerja Pegawai Terhadap Kualitas Pelayanan Pemerintahan di Kecamatan Rappocini Kota Makassar - Haerana, Haerana; Sari, Trilya Buana; Razak, Andi Rosdianti; Hamrun, Hamrun (Kybernology : Journal of Government Studies, 2022)
This study aims to determine the effect of employee performance on the quality of public services at the Rappocini District office. This study uses quantitative research methods as an effort to investigate the problem. The population in this study were all visitors and employees (State Civil Apparatus) at the Rappocini District office, totaling 54 people. Methods of data analysis using descriptive analysis and simple regression analysis. The results of this study indicate that (1) The results of the research conducted indicate that the performance of employees in the Rappocini District, especially the Rappocini District, can be said to be good, (2) The results of the research conducted indicate that the quality of service in the Rappocini District is good, (3) The results simple linear regression test, R2 test, and F test show that employee service performance has a significant influence on the quality of administrative services with a positive regression coefficient direction. Thus the results of testing for the hypothesis are accepted and mean that employee service performance has a positive and significant effect on the quality of administrative services at the Rappocini District office. The results of the analysis of employee performance variables are in the good category with an average score of 211.8 and the variable analysis of the quality of public services is in the good category with an average score of 2.36. Based on the results of the simple linear regression test, it shows that employee performance variables have an effect of 5.29% on the quality of administrative services at the Rappocini Sub-District Office, Makassar City.